The effect of progressive resistance training on the blood lipid profile in post-menopausal women - Viljoen, Janet Erica (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2009)
The main purpose of this study was to assess the effect of progressive resistance training on the blood lipid profile in post-menopausal women. Thirty-four female subjects aged 50 to 75 years were selected from the population of Grahamstown, South Africa. All participants were previously sedentary and possessed at least one lipid profile abnormality but were otherwise healthy. Pre-tests included a sub-maximal stress Electrocardiogram, measures of stature, mass, central and limb girths as well as an oral glucose tolerance test (OGTT) and a total blood lipid profile. Participants took part in a 24-week progressive resistance training programme, consisting of three supervised sessions per week, each lasting 45 minutes and were not permitted to lose more than 10% of initial body mass during the 24-week study. All pre-test measures, excluding the stress ECG and the OGTT, were repeated every four weeks for the duration of the study. Results were that body mass, body mass index and waist-to-hip ratio did not change. Girth measures at mid-humerus, chest, waist, hip, mid-quadricep and mid-gastrocnemius all decreased significantly (p=0.05). LDL-cholesterol increased significantly over the course of 24 weeks (3.61mmol.L-1 to 4.07mmol.L-1) as did total cholesterol (5.81mmol.L-1 to 6.24mmol.L-1). Triglyceride concentration remained unchanged and HDL-cholesterol decreased significantly between the pre-test measure (1.55mmol.L-1) and the measure after six months (1.42mmol.L-1). It can be concluded that the blood lipid profile in a sample of post-menopausal women was not positively affected by a progressive resistance training programme over a 24 week period.,Maiden name: Kelly, Janet Erica
Keywords: Weight training for women -- Physiological aspects; Weight training -- Physiological aspects; Exercise for women -- Physiological aspects; Physical fitness for women -- Physiological aspects; Energy metabolism; Middle aged women -- Health and hygiene